The Efforts of the Natural Resources Conservation Agency in Attracting Tourists in Kapuas Hulu Regency - Heriyanto Heriyanto; Muhammad Adib Alfarisi; Melti Oktavianda (Enrichment : Journal of Management, 2022)
This study is keen to determine the works of BKSDA (Natural Resources Conservation Agency) in promoting tourism as well as supporting and inhibiting aspects in the development of ecotourism in Danau Sentarum National Park. The study applied a descriptive-qualitative method. Based on the Presidential Regulation of the Republic of Indonesia No. 3 of 2012, Danau Sentarum National Park is designated as a centre for developing ecotourism and cultural tourism and has the potential to be developed as an ecotourism object. However, it has not yet developed properly to reach its desired local and international tourism potential. The research findings are as follows: (1) the supporting factors for the development of ecotourism in Danau Sentarum National Park are its natural landscape and fresh air, local government and communities sponsorship; (2) The inhibiting factors for the tourism object of Danau Sentarum National Park for becoming a prime destination for tourism are: the lack of facilities and poor infrastructure, difficulties in accessing the National Park due to its distance from the capital city of West Kalimantan Province, lack of talented human resources from both local communities and the personnel of BKSDA, and sources of staple materials and clean water are challenging to reach, and; (3) The works of BKSDA are to develop facilities and infrastructure, provide proper services to tourists, and improve accessibility. The study concludes that Danau Sentarum ecotourism is a prospective tourist attraction that must be managed more optimally, and it needs collaborative efforts between the local government and the surrounding communities.